GAMIFICATION OF LIBRARY ORIENTATION AND INFORMATION LITERACY SKILLS TRAINING IN ACADEMIC LIBRARIES - Vivian Ukachi Nwaobasi; Christiana Nneka Chigor; Chukwuemerie Ernest Obiora; Josiah Ibezim Ekwebelem (INJOSEDU: International Journal of Social and Education, 2026)
Gamification is a recent teaching technique in academic libraries that is turning the conventional library orientation and information literacy (IL) training into engaging, student-centred learning experiences. This research investigates the use of gamification design elements (points, badges, quests and leaderboards) in library instruction to improve student engagement, motivation, and learning. Building on existing learning theories, such as Self-Determination Theory, Constructivism, Experiential Learning, and Behaviourism, the paper proposes a theoretical model of gamification design and IL. The research takes a conceptual and design-based approach to examine the effects of gamified activities on user experiences and learning. The study reveals that gamification enhances library use, enhances IL skills and engages users in learning. The research finds that gamification is an effective and scalable teaching strategy which transforms academic libraries into active learning spaces that support academic achievement and lifelong learning.